Cre stoplight a red/green fluorescent reporter of Cre recombinase expression in living cells - Yang, Y S (BioTechniques, 2001)
The Cre/lox system is a powerful genetic tool with which to manipulate the genome. Here, we describe the development of a simple reporter system for Cre recombinase, called the Cre Stoplight. In the absence of Cre, the red fluorescent protein is expressed; when Cre catalyzes a recombination event, the green fluorescent protein is produced. Testing this system in transiently transfected cells showed that it produced robust signals (90% of the cells converted from red to green) when equal amounts of the plasmids encoding Cre recombinase and the Cre Stoplight were used. A 1:100 ratio of enzyme to reporter plasmid produced similar results, and a 1:10000 ratio was necessary to significantly reduce the number of cells converting to green (1%)